High-productive source of the cathodic vacuum-arc plasma with the rectilinear filter - Vasylyev, V.V.; Luchaninov, A.A.; Strel’nitskij, V.E. (Вопросы атомной науки и техники, 2013)
The design and performance of high productive cathodic vacuum arc plasma source with rectilinear “magnetic
island” filter, which is suitable for industrial applications, are briefly described. The device is characterized by
achievable output ion current up to 4 A at an arc current of 100 A, Ti coating deposition rate at a distance of
150 mm from the outlet is 20 micron/hour within the circle of 180 mm diameter. In terms of productivity and quality
of plasma purification from particulates the developed plasma source is superior to world analogues by 1.5...2 times. Приведено краткое описание конструкции и характеристик высокопроизводительного, пригодного для
промышленного применения, вакуумно-дугового источника плазмы с прямолинейным фильтром типа
«магнитный остров». Достижимый выходной ионный ток источника – 4 А при токе дуги 100 А. Скорость
осаждения Ti-покрытия на расстоянии 150 мм…20 мкм/ч в пределах круга диаметром 180 мм. По
производительности и качеству очистки от макрочастиц разработанное устройство превосходит мировые
аналоги в 1,5…2 раза. Наведено скорочений опис конструкції та характеристики високопродуктивного, придатного для
промислового застосування, вакуумно-дугового джерела плазми з прямолінійним фільтром типу «магнітний
острів». Досяжний вихідний іонний струм джерела – 4 А при струмі дуги 100 А. Швидкість осадження
Ti-покриття на відстані 150 мм…20 мкм/год у межах кола з діаметром 180 мм. За продуктивністю та якістю
очищення від макрочасток розроблений пристрій перевершує світові аналоги в 1,5…2 рази.